High-performance hollow brick based on modified gasification slag and preparation method thereof
Through acid modification, gasified slag and coal gangue are treated, and combined with other modified materials and processes, the problems of insufficient strength, water absorption and freezing resistance of hollow bricks are solved, efficient resource utilization and low-energy production are achieved, and the needs of high-performance building materials are met.
Patent Information
- Application Number
- CN202411908341.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing hollow bricks are insufficient in strength, water absorption and frost resistance, and the traditional process consumes high energy and cost, making it difficult to meet the needs of high-performance building materials.
By acid-modifying the gasified slag and coal gangue, impurities are removed, active components are activated, and the formulation and process are optimized, using low-temperature sintering process and hydraulic molding technology.
It significantly improves the compressive strength, water absorption and frost resistance of hollow bricks, reduces manufacturing costs and production energy consumption, and realizes efficient resource utilization of industrial solid waste, which is suitable for the needs of high-performance building materials.
Smart Images

Figure CN119683969A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building materials, and specifically relates to a high-performance hollow brick based on modified gasified slag and a preparation method thereof, which is particularly suitable for resource utilization of industrial solid waste and preparation of lightweight and high-strength building materials. Background Art
[0002] With the rapid development of industrialization, coal gasification technology has been widely used in the modern coal chemical industry, and its by-product, gasified slag, is usually treated as solid waste. At present, the utilization of gasified slag and coal gangue is relatively single, mainly used as low-value-added fillers, while the application in the field of high-value-added building materials is still in its early stages. At the same time, existing hollow brick products generally have problems such as insufficient compressive strength, high thermal conductivity, poor durability, high water absorption, and poor antifreeze performance, which makes it difficult to meet the demand for high-performance building materials in modern buildings. Therefore, it is of great significance to develop a high-performance hollow brick preparation technology that efficiently utilizes gasified slag.
[0003] In the prior art, the amount of solid waste added to the formula of building bricks is usually low, and most of them are single components (gasified slag is about 20% to 40%; coal gangue is about 10% to 30%). This is mainly because the chemical inertness and physical instability of the original gasified slag limit its good reaction ability with other components. The direct use of gasified slag will lead to problems such as decreased mechanical properties of the brick body and increased water absorption. At the same time, the gasified slag particles are unevenly distributed and have high porosity, which leads to uneven mixing and increased water absorption of the product, thereby affecting the frost resistance and durability of the brick body. In addition, the traditional preparation process is mainly based on high-temperature sintering, which not only has high energy consumption and high cost, but also seriously affects the feasibility of large-scale promotion and application.
[0004] The limitations of gasified slag as a solid waste are reflected in many aspects. First, the chemical inertness of gasified slag is high, the activity is insufficient, and it cannot effectively participate in the reaction or provide sufficient bonding, which limits its effect in high-proportion applications. Secondly, its structure is porous and rough, resulting in a decrease in the mechanical properties of the product and insufficient strength of the green body. In addition, gasified slag contains impurities such as unburned carbon and sulfides, which may release harmful gases during high-temperature treatment and affect the quality of sintered products. On the other hand, the high-proportion incorporation of solid waste materials such as gasified slag and coal gangue also faces challenges. These solid waste materials have a high porosity and a loose internal structure, which makes it easy to form open pores or capillaries inside the product, increase water absorption, and reduce antifreeze performance. At the same time, the introduction of a high proportion of solid waste may cause uneven mixing, poor particle bonding, and large fluctuations in product performance. In addition, the modification of solid waste usually requires additional costs, making the application of a high proportion of solid waste economically disadvantageous.
[0005] In summary, the long-term accumulation of gasified slag as waste not only occupies land, but also pollutes the environment. Traditionally prepared hollow bricks have problems such as low strength and poor thermal insulation, which make it difficult to meet the demand for high-performance building materials. Therefore, it is urgent to develop a high-performance hollow brick preparation technology that can efficiently utilize gasified slag, and solve the problems of low solid waste utilization, insufficient performance and limited economy by optimizing the formula and process, so as to achieve the dual goals of resource utilization and environmental protection. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance hollow brick based on modified gasified slag and a preparation method thereof, so as to solve the deficiencies of existing hollow bricks in strength, water absorption rate and frost resistance, and at the same time realize the efficient resource utilization of industrial solid wastes such as coal gangue and gasified slag.
[0007] The high-performance hollow brick based on modified gasified slag provided by the present invention is made of the following components in weight percentage: 50% to 60% of modified gasified slag, 15% to 20% of modified coal gangue powder, 15% to 20% of clay, 3% to 7% of limestone powder, 2% to 5% of silica fume, and 0.5% to 1% of auxiliary additives.
[0008] The modified gasified slag is prepared by soaking the gasified slag in a 0.1-0.5 mol / L sulfuric acid aqueous solution at 80-90° C. for 20-24 hours, washing, drying, and grinding to a particle size of no more than 5 mm. The preferred volume ratio of the gasified slag to the sulfuric acid aqueous solution is 1:10-15.
[0009] The modified gangue powder is prepared by soaking the gangue powder in a 0.1-0.5 mol / L sulfuric acid aqueous solution at 80-90° C. for 20-24 hours, washing, drying, and grinding to a particle size of no more than 100 μm. The preferred volume ratio of the gangue powder to the sulfuric acid aqueous solution is 1:10-15.
[0010] The auxiliary additives are composed of a binder, a reinforcing agent and a foaming agent. Taking the weight percentage of the hollow brick as 100%, the binder is 0.1% to 0.5%, the reinforcing agent is 0.1% to 0.5%, and the foaming agent is 0.1% to 0.5%.
[0011] Furthermore, it is preferred that the binder is polyvinyl alcohol 17-88, the reinforcing agent is HL-200 hydrophilic fumed silica, and the foaming agent is GLS-65 aqueous aluminum powder paste.
[0012] The method for preparing high-performance hollow bricks based on modified gasified slag of the present invention comprises the following steps:
[0013] Step 1: The gasified slag and the coal gangue are crushed respectively so that the particle size of the gasified slag does not exceed 5 mm, and the particle size of the coal gangue does not exceed 10 mm; the crushed gasified slag and the crushed coal gangue are respectively placed in a 0.1-0.5 mol / L sulfuric acid aqueous solution at 80-90° C. for 20-24 hours, and then washed and dried; the dried gasified slag is ground to a particle size of no more than 5 mm to obtain modified gasified slag; the dried coal gangue is ground to a particle size of no more than 100 μm to obtain modified coal gangue powder.
[0014] Step 2: Add modified gasified slag, modified coal gangue powder, clay, limestone powder, silica fume, auxiliary additives and water into a mixer, stir them evenly, control the moisture content of the mixture to 15% to 20%, and dry them.
[0015] Step 3: Place the dried mixture from step 2 into a mold and press it into shape using a hydraulic press to obtain a brick.
[0016] Step 4: Place the formed bricks in a tunnel kiln or a rotary kiln, gradually raise the temperature to 850-950°C, bake at a constant temperature for 8-12 hours, and then cool to room temperature to obtain hollow bricks.
[0017] In the above step 2, the temperature of the drying treatment is 100-120°C.
[0018] In the above step 3, a hydraulic press is used to perform compression molding at a pressure of 10 to 20 MPa.
[0019] The beneficial effects of the present invention are as follows:
[0020] 1. The present invention effectively removes soluble salts, sulfides and other impurities by acid-modifying gasified slag and coal gangue, and activates the silicon and aluminum active components in gasified slag and coal gangue, significantly enhancing their chemical bonding ability with clay or other components. In the acid modification process, the particle size (≤5mm) is controlled by screening and crushing, and coarse particles and some pores are eliminated, thereby improving the uniformity and bulk density of the material. After modification, the chemical activity and particle distribution of gasified slag and coal gangue are significantly optimized, the bonding force between particles and the overall mechanical properties are enhanced, and gasified slag and coal gangue can be used in brick making at a total ratio of up to 65% to 80%, while ensuring the strength and stability of the brick body. In addition, acid modification activates the silicon and aluminum oxides in gasified slag and coal gangue, allowing them to fully react with the binder and other components to form a stable silicate and aluminate structure, thereby improving the strength and density of the brick body. The modification treatment also effectively reduces the porosity and soluble salt content of gasified slag and coal gangue, improves the frost resistance and service life of the brick body, and solves problems such as decreased strength, increased water absorption and sintering cracks that may occur when high dosages are used.
[0021] 2. The present invention uses polyvinyl alcohol (PVA17-88) which is inexpensive and suitable for acidic environments as a binder, which can significantly improve the bonding strength of the mixture at a low addition amount (0.1% to 0.5%), thereby ensuring the stability of the brick. At the same time, HL-200 hydrophilic fumed silica is introduced as a reinforcing agent, which reacts with acid-modified gasified slag during the sintering process to form a dense silicate structure, which not only improves the compressive strength of the brick body, but also enhances durability. In addition, a uniform pore structure is formed under acidic conditions through an aluminum powder foaming agent (GLS-65 water-based aluminum powder paste), which reduces the density of hollow bricks and improves thermal insulation performance. This raw material selection combines economy and functionality, and is suitable for large-scale production needs.
[0022] 3. The present invention adopts a low-temperature sintering process (850-950°C), which reduces production energy consumption while improving the stability of brick performance. By optimizing the molding pressure (10-20MPa) and firing temperature, the compressive strength, impermeability resistance and durability of hollow bricks are effectively improved. In addition, impurities such as unburned carbon and soluble salts are removed during the acid modification process, which significantly improves the uniformity of the sintered material. The formula introduces modified coal gangue powder, clay, limestone powder, silica fume and other raw materials in a scientific proportion to form a synergistic effect, which greatly improves the comprehensive performance of hollow bricks, including high strength, low water absorption and excellent antifreeze performance, which is suitable for construction needs in cold areas. At the same time, the present invention designs a simple and easy preparation process to facilitate industrial production.
[0023] 4. The modified gasified slag dosage of the present invention is as high as 50% to 60%, which is much higher than the existing market formula of 30% to 40%, realizing the efficient utilization of solid waste resources, reducing the dependence on natural clay and other raw materials, and thus reducing the environmental burden of industrial waste. The final product has higher compressive strength (10 to 12 MPa), low water absorption (less than 16%) and excellent antifreeze performance, meeting or even exceeding the performance indicators of traditional gangue bricks and gasified slag bricks. The present invention significantly reduces manufacturing costs, production energy consumption, and environmental burden by optimizing the formula and process, fully reflecting the economy and environmental protection. Under the guidance of the concepts of efficient resource utilization, clean production and circular economy, the present invention is of great significance to promoting the green development of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the appearance structure of the hollow brick prepared in Example 1.
[0025] Figure 2 This is a SEM microscopic scan of the hollow brick prepared in Example 1.
[0026] Figure 3 This is a SEM microscopic scan of the hollow brick prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0028] Example 1
[0029] The hollow bricks of this embodiment are made of the following components in weight percentage: 55% modified gasified slag, 20% modified coal gangue powder, 15% clay, 5% limestone powder, 4% silica fume, 0.5% polyvinyl alcohol 17-88, 0.3% HL-200 hydrophilic fumed silica, and 0.2% GLS-65 aqueous aluminum powder paste.
[0030] The structure of the hollow brick in this embodiment is as follows Figure 1 As shown, the specific preparation method is as follows:
[0031] Step 1: The coal chemical waste gasification slag and coal gangue are crushed separately to make the gasification slag particle size no more than 5mm and the coal gangue particle size no more than 10mm. The crushed gasification slag is placed in a 0.5mol / L sulfuric acid aqueous solution, soaked at 80°C for 23 hours, then filtered, washed, dried and ground to a particle size no more than 5mm to obtain modified gasification slag. The crushed coal gangue powder is placed in a 0.5mol / L sulfuric acid aqueous solution, soaked at 80°C for 23 hours, then filtered, washed, dried and ground to a particle size no more than 100μm to obtain modified coal gangue powder.
[0032] Step 2: Add modified gasified slag, modified coal gangue powder, clay, limestone powder, silica fume, polyvinyl alcohol 1788, HL-200 hydrophilic fumed silica, GLS-65 aqueous aluminum powder paste and water into a mixer according to the above weight percentage ratio, stir well, control the moisture content of the mixture to 20%, and dry it at 120°C.
[0033] Step 3: Place the mixture dried in step 2 into a mold and use a hydraulic press to press it at a pressure of 15 MPa to obtain a brick.
[0034] Step 4: Place the formed bricks in a tunnel kiln, gradually raise the temperature to 900°C, bake at a constant temperature for 12 hours, and then cool to room temperature to obtain hollow bricks.
[0035] Comparative Example 1
[0036] The modified gasified slag in Example 1 is directly replaced by the original unmodified gasified slag, and the modified coal gangue powder is directly replaced by the original unmodified coal gangue powder. Other raw materials and amounts are the same as in Example 1. The structure and specific preparation method of the hollow bricks are also the same as in Example 1.
[0037] Example 2
[0038] The modified gasified slag in Example 1 was replaced with the following proportions: modified gasified slag 60%, modified coal gangue powder 15%, clay 15%, limestone powder 5%, silica fume 4%, polyvinyl alcohol 1788 0.5%, HL-200 hydrophilic fumed silica 0.3%, GLS-65 aqueous aluminum powder paste 0.2%. The structure and specific preparation method of the hollow brick are the same as those in Example 1.
[0039] The properties of the hollow bricks prepared in the above Examples 1 to 2 and Comparative Example 1 were tested, and the specific testing method is as follows:
[0040] (1) Compressive strength test: According to the Test Methods for Sintered Bricks and Blocks (GB / T 2542-2012), a universal material testing machine was used to apply load to the hollow bricks, and the load value at failure was recorded and the compressive strength was calculated.
[0041] (2) Water absorption test: measure the difference in quality between dry bricks and water-saturated bricks.
[0042] (3) Volume density test: Measure the mass (m) and volume (V) of the brick, according to the formula: density (g / cm 3 )=m / V, calculate the volume density.
[0043] The test results are shown in Table 1.
[0044] Table 1
[0045] Performance Indicators Example 1 Comparative Example 1 Example 2 Compressive strength(MPa) 11.5 7.8 10.8 Water absorption (%) 13.8 21.3 14.5 <![CDATA[Bulk density (g / cm 3 )]]> 1.65 1.42 1.62
[0046] From Table 1, Figure 2 , Figure 3 It can be seen that under the same raw material dosage ratio and preparation method, the compressive strength of the hollow bricks prepared by the unmodified gasified slag and coal gangue powder in Comparative Example 1 is significantly lower than that of the hollow bricks prepared by the gasified slag and coal gangue powder after sulfuric acid modification in Example 1, the water absorption rate is greatly increased, and the structural stability is poor. This is because the activity of the gasified slag and coal gangue powder is improved and the impurity content is reduced after sulfuric acid modification. After sintering, the particle interface is more tightly bonded, the porosity is reduced, and the brick performance is significantly improved. In Example 2, the proportion of modified gasified slag is increased, and the hollow bricks obtained at a high proportion of 60% are still significantly better than those in Comparative Example 1, which meets the GB / T 2542-2012 standard.
Claims
1. A high-performance hollow brick based on modified gasified slag, characterized in that: The hollow brick is made of the following components in weight percentage: 50% to 60% of modified gasified slag, 15% to 20% of modified coal gangue powder, 15% to 20% of clay, 3% to 7% of limestone powder, 2% to 5% of silica fume, and 0.5% to 1% of auxiliary additives; The modified gasified slag is prepared by soaking the gasified slag in a 0.1-0.5 mol / L sulfuric acid aqueous solution at 80-90° C. for 20-24 hours, then washing, drying, and grinding to a particle size of no more than 5 mm. The modified coal gangue powder is prepared by soaking the coal gangue powder in a 0.1-0.5 mol / L sulfuric acid aqueous solution at 80-90° C. for 20-24 hours, washing, drying, and grinding to a particle size not exceeding 100 μm.
2. The high performance hollow brick based on modified gasified slag according to claim 1, characterized in that: The auxiliary additives consist of a binder, a reinforcing agent and a foaming agent.
3. The high performance hollow brick based on modified gasified slag according to claim 2, characterized in that: Taking the weight percentage of the hollow brick as 100%, the binder accounts for 0.1% to 0.5%, the reinforcing agent accounts for 0.1% to 0.5%, and the foaming agent accounts for 0.1% to 0.5%.
4. The high performance hollow brick based on modified gasified slag according to claim 2 or 3, characterized in that: The binder is polyvinyl alcohol 17-88, the reinforcing agent is HL-200 hydrophilic fumed silica, and the foaming agent is GLS-65 aqueous aluminum powder paste.
5. The high performance hollow brick based on modified gasified slag according to claim 1, characterized in that: During the preparation of the modified gasified slag, the volume ratio of the gasified slag to the aqueous sulfuric acid solution is 1:10-15.
6. The high performance hollow brick based on modified gasified slag according to claim 1, characterized in that: In the preparation process of the modified coal gangue powder, the volume ratio of the coal gangue powder to the sulfuric acid aqueous solution is 1:10-15.
7. A method for preparing high-performance hollow bricks based on modified gasified slag according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: crushing the gasified slag and the coal gangue respectively, so that the particle size of the gasified slag does not exceed 5 mm, and the particle size of the coal gangue does not exceed 10 mm; soaking the crushed gasified slag and the crushed coal gangue in a 0.1-0.5 mol / L sulfuric acid aqueous solution at 80-90° C. for 20-24 hours, respectively, and then washing and drying; grinding the dried gasified slag to a particle size of no more than 5 mm to obtain modified gasified slag; grinding the dried coal gangue to a particle size of no more than 100 μm to obtain modified coal gangue powder; Step 2: Add modified gasified slag, modified coal gangue powder, clay, limestone powder, silica fume, auxiliary additives and water into a mixer, stir them evenly, control the moisture content of the mixed material to 15% to 20%, and dry them; Step 3: Put the mixture after drying in step 2 into a mold and press it into shape using a hydraulic press to obtain a brick; Step 4: Place the formed bricks in a tunnel kiln or a rotary kiln, gradually raise the temperature to 850-950°C, bake at a constant temperature for 8-12 hours, and then cool to room temperature to obtain hollow bricks.
8. The method for preparing high-performance hollow bricks based on modified gasified slag according to claim 7, characterized in that: In step 2, the temperature of the drying treatment is 100-120°C.
9. The method for preparing high-performance hollow bricks based on modified gasified slag according to claim 7, characterized in that: In step 3, a hydraulic press is used to press-form the product at a pressure of 10 to 20 MPa.
Citation Information
Cited By
Coal gangue lightweight aggregate self-curing lightweight concrete and preparation method thereof
CN119430774A